Implementation of 5D Building Information Modelling (BIM) System on Quay Wall Structure By Paying Attention to Clash Detection (Case Study: Project Patimban Package 6) - Ruri Welda Palensia; Endah Kurniyaningrum; M. Zaki M. Zaki; Darmawan Pontan (Green Publisher Indonesia, 2024)
Building Information Modeling (BIM) is one of the technologies in the field of AEC (Architecture, Engineering and Construction) that is able to simulate all information in a development project into a 3D model. Research in this thesis was carried out to analyze the results of the implementation of Building Information Modelling (BIM) 5D in dock work (Quay Wall Structure) by paying attention to clash detection at the pre-construction stage, with a case study of the Patimban Port Project Package 6. The focus of the research is the application of BIM 5D in identifying and resolving design clashes that can have an impact on the estimation of work volume and cost. The method used is qualitative and inductive analysis using Tekla Structure 2021 BIM software for 3D modeling and clash detection identification. The results of clash detection identification are grouped into three categories, namely large, medium, and small. The implementation of BIM 5D shows significant volume changes in some work items. The volume of the Deck Slab (Pier Head) and Front Wall decreased compared to the initial RAB, while the volume of the Deck Slab (In-Situ Concrete) increased. The cost comparison shows a savings of 7.06% of the total initial cost of RAB Quay Wall Structure, which is equivalent to IDR 10,502,919,303.55. The implementation of BIM 5D by conducting clash detection is quite effective in identifying and resolving design clashes, mitigating errors and revisions when entering the construction stage, and can increase project efficiency in better communication and coordination.